1987
DOI: 10.1080/02724936.1987.11748503
|View full text |Cite
|
Sign up to set email alerts
|

Acute illness in Nigerian children with sickle cell anaemia

Abstract: The pattern of illness in 60 consecutive children with homozygous sickle cell disease who attended the Paediatric Emergency Room of a busy Lagos hospital with acute illness was studied prospectively. Their ages ranged from 3 months to 13 years with a peak in the 2nd year. There were twice as many boys as girls. The commonest symptoms were fever, limb or abdominal pain and cough, and the commonest signs were pallor and hepatomegaly. Painful crises occurred in 27, anaemic crises in 11, and a combination of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
3

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 4 publications
1
42
3
Order By: Relevance
“…Even though the chronic daily use of opioids in SCD patients with frequent severe painful episodes is controversial, many clinicians report that patients improved and function better after treatment with opioid analgesics. [29] Others are concerned about the symptoms of withdrawal, along with exacerbation or lack of recognition of interacting factors such as depression, anxiety, or intolerable life stresses. Physicians have been identified to greatly over-estimate the incidence of addiction in patients with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the chronic daily use of opioids in SCD patients with frequent severe painful episodes is controversial, many clinicians report that patients improved and function better after treatment with opioid analgesics. [29] Others are concerned about the symptoms of withdrawal, along with exacerbation or lack of recognition of interacting factors such as depression, anxiety, or intolerable life stresses. Physicians have been identified to greatly over-estimate the incidence of addiction in patients with SCD.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the morbidity pattern of homozygous sickle cell anaemia, Kaine 11 did not find any case of acute splenic sequestration crises among her patients. However Akinyanju and colleagues 10 in Lagos, had noted that splenomegaly was significantly associated with severe anaemia in patients with sickle cell disease. They concluded that this probably reflected the well known blood sequestrating propensity of that organ.…”
Section: Discussionmentioning
confidence: 99%
“…S pneumoniae did not occur in any of 19 patients with bacteraemia in Lagos6 and was seen in only one among 54 patients in Benin City 7. Nor did it occur among 304 children admitted with acute illness in Kaduna,8 although the organism was isolated from the cerebrospinal fluid in three children.…”
mentioning
confidence: 83%
“…Early reports from the then Belgian Congo and from Nigerian adults noted a high prevalence of S pneumoniae. 4 – 5 However, more recent studies of children with septicaemic sickle cell disease in Nigeria68 and Uganda (Monica Etima, personal communication, 2004) have found that less than 10% of septicaemias were due to this organism and that septicaemia due to Staphylococci, Escherichia coli, Salmonella , and Klebsiella predominated.…”
mentioning
confidence: 99%